A comprehensive review of microstructure evolution during friction stir welding of aluminium to copper. (2018) - Medhi, Tanmoy; Roy, Barnik Saha; Saha, Subhash Chandra
The present review paper focuses on the various researches done in joining of aluminium and copper by friction stir welding (FSW). Being a solid state process, FSW has proven to efficiently join aluminium and copper which is extensively used in power generation, electrical and electronic industry. However, it is a challenge to achieve a good quality welded joint of aluminium and copper due to the difference in properties of both the materials. The present review paper comprehensively reports the study of microstructure and its evolution during the process. Also, an assessment of the formation of different intermetallic compounds (IMCs) during the process and the effect of various process parameters like rotational speed, tool traverse speed, the arrangement of base materials, offset and tool geometry on the IMCs and microstructure evolution is given.